ANALISA KESEIMBANGAN LINTASAN PERBANDINGAN METODE RPW DENGAN REGION APPROACH DALAM PEMBUATAN BATIK PRINTING DI “SEKAR JATI STAR” - Muhammad Sobir Farid; Sulung Rahmawan Wira Ghani (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2021)
This Sekar Jati Star Written Batik is a type of company that is still an SME or Home Industry with a wholesale production type or every time you receive orders, and the Sekar Jati Star Batik UKM is a company that adheres to a job shop because of the variety of products or different motives with different flow patterns. different too, so this industry practice research carries the topic of line balancing using the RPW method and the Region Approach, namely to find out that the production line balance problem occurs most in the assembly process compared to the manufacturing process. Continuous movement is most likely achieved by manual assembly operations when several operations can be divided by a short duration in the batik printing process so that the distribution of tasks can be evenly distributed so that jams can be avoided. After calculating the RPW method, the results of the number of stations in the initial condition are 5 and the RPW method 5, the balance delay in the initial conditions is 39.2% with the RPW method to 18.0%, the efficiency of the initial condition system is 60.8% with the RPW method 82%, Output Production Initial conditions 16 meters / day with the RPW method 31 meters / day. Then the calculation of the Region Approach method results in the number of work stations 5, Balance Delay 96%, and for work efficiency 0.0376 or 4%.